Reference intervals of the sex hormonal profile in healthy women: A retrospective single-center study in Peru - Moya-Salazar, Jeel (2022)
The female hormonal profile is of utmost importance for the assessment of the endocrinological functional status and the diagnosis of diseases. The analysis must delimit their normality intervals based on the manufacturer's cut-off points. Due to not all intervals can be evaluated before use, it is imperative to verify the reference intervals to achieve uniformity in the interpretation of results in the female population. We determine the reference intervals of five female sex hormones [Follicle Stimulating hormone (FSH), Estradiol, Luteinizing Hormone (LH), Prolactin, and progesterone] using electrochemiluminescence in the Cobas e411 (Roche). We included female patients >18 years old, between the 3rd and 15th day of the menstrual cycle (follicular phase) and had no previous medical history or recent medication. For reference intervals analysis, we followed the recommendations of the CLSI C28-A3 guideline. The average concentration for FSH, progesterone, LH, prolactin and estradiol were 11.48 ± 21.10 mIU/ml, 8.19 ± 11.90 ng/ml, 10.98 ± 11.55 ng/ml, 25.05 ± 32.74 ng/mL, and 147.08 ± 473.8 pmol/mL, respectively. Eighty per cent of parameters showed a satisfactory transfer for the manufacturer's reference intervals, except for estradiol, which had 85.5% of transferred values. Our results suggest that 4/5 sex hormones were found within the manufacturer's reference intervals and can be quantified in Peruvian women, ensuring the quality of their results. However, it is necessary to determine the estradiol with other reagents and assays since we show errors in the transfer of intervals.